2014
DOI: 10.12659/msm.890804
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Metastatic Lymph Node Ratio in Non-Metastatic, Lymph Node-Invaded Colon Cancer: A Clinical Trial

Abstract: BackgroundThe aim of this study was to evaluate the prognostic importance of the metastatic lymph node ratio for stage III colon cancer patients and to find a cut-off value at which the overall survival and disease-free survival change.Material/MethodsPatients with pathological stage III colon cancer were retrospectively evaluated for: age; preoperative values of Crp, Cea, Ca 19-9, and Afp; pathologic situation of vascular, perineural, lymphatic, and serosal involvement; and metastatic lymph node ratio values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 18 publications
1
51
0
Order By: Relevance
“…Because hypothyroidism has pro-oxidative and inflammatory potential, it may trigger carcinogenesis [24,25]. The linear positive correlations observed in this study between TSH and TC, LDL-C, non-HDL-C, and TGs are consistent with the proatherogenic potential of hypothyroidism.…”
Section: Discussionsupporting
confidence: 78%
“…Because hypothyroidism has pro-oxidative and inflammatory potential, it may trigger carcinogenesis [24,25]. The linear positive correlations observed in this study between TSH and TC, LDL-C, non-HDL-C, and TGs are consistent with the proatherogenic potential of hypothyroidism.…”
Section: Discussionsupporting
confidence: 78%
“…5) For breast cancer, there was an inverse connection with serum calcium [21], as well as no association with serum calcium. 6) HPT was also associated with the development of colon cancer [22] as well as gastric carcinoma [23]. To date, the correlation between thyroid cancer and serum calcium level remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In research on small cell lung cancer, Levy et al reported that the proliferation and metastasis of advanced tumors are suppressed after splenectomy [14]. Isik et al demonstrated that because the metastatic lymph node ratio is decreased by resecting the perisplenic lymph nodes, survival may be increased by splenectomy [15,16]. A similar phenomenon was also reported in a study of diffuse large B cell lymphoma [17].…”
Section: Discussionmentioning
confidence: 67%